O ouro do mar: do surgimento da indústria da pesca da lagosta no Brasil à condição do pescador artesanal na História do tempo presente (1955-2000). Uma narrativa sócio-histórico marítima - Muniz, Túlio de Souza (2005)
The present work deals with the condition of the artisan fishing at the present, of the apropriate of knowledge originated of the confrontation between the artisan fishing and the industrial fishing. The reflections follow around the history of the implantation of industrial fishing in Brazil from the lobster fishing at 1950, standing out an international conflict between Brazil and France in the 1960 and the relation of the artisan fisherman with these events. Finally to look for understand the daily of the fisherman who confrot with alterations of knowledge and at the environment provoked by the facts.